2021
DOI: 10.1002/2211-5463.13157
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein M promotes cholesterol uptake and efflux from mouse macrophages

Abstract: Apolipoprotein M (ApoM) exhibits various anti-atherosclerotic functions as a component of high-density lipoprotein (HDL) particles. Scavenger receptor class B type I (SR-BI) is a classic HDL receptor that mediates selective cholesterol uptake and enhances the efflux of cellular cholesterol to HDL. However, the effect of ApoM on cholesterol transport in macrophages remains unclear. In this study, we identified for the first time that ApoM is expressed in mouse macrophages and is involved in cholesterol uptake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A recent study suggests that apoM is an essential driver for functional cholesterol uptake and efflux in mouse macrophages via SR-BI. Herein, apoM-rich HDL mediated higher cholesterol efflux compared to apoM-deficient HDL [28]. However, the discovery of the apoM/S1P-complex paved the ground for substantial research to use the beneficial properties of S1P-signaling as a potential therapeutic target for CVD.…”
Section: The Crossroad Between Apom S1p and Hdlmentioning
confidence: 99%
“…A recent study suggests that apoM is an essential driver for functional cholesterol uptake and efflux in mouse macrophages via SR-BI. Herein, apoM-rich HDL mediated higher cholesterol efflux compared to apoM-deficient HDL [28]. However, the discovery of the apoM/S1P-complex paved the ground for substantial research to use the beneficial properties of S1P-signaling as a potential therapeutic target for CVD.…”
Section: The Crossroad Between Apom S1p and Hdlmentioning
confidence: 99%
“…Concordant results were obtained in Apom -deficient mice which present impaired insulin sensitivity, high plasma inflammatory markers such as IL-6 or IL-1β, and hepatic NF-κB [ 99 , 107 ]. Yao et al also recently demonstrated that APOM is expressed in murine and human macrophages, interacts with the scavenger receptor BI to promote cholesterol efflux from the phagocytic cells and protects against atherosclerosis [ 108 , 109 ]. More, Apom -deficient mice display blood hypertension and cardiac hypertrophy compared to wildtype animals [ 110 ].…”
Section: Apommentioning
confidence: 99%